(untitled) (Law and world, 2023)
Secured Credit Transactions (SCTs) are necessary and unavoidable transactions that business owners engage in to ensure their businesses thrive. However, because of the possibility that a person seeking to take a loan may be desperate and be taken advantage of in a time of dire need, or on the other hand, the possibility that the party may present fake properties as security for the loan, there are legal requirements that both the debtor and the creditor must meet. This paper addresses the possible parties to the SCT and the condition each category of the party must meet for the transaction to be valid. It further identifies the measures to be implemented to ensure the validity of Secured Credit Transactions. This paper finds that Nigerian Law protects both the creditor and the debtor to ensure that the SCT does not fail and none of the parties run at a loss. This paper concludes that there is a need to further protect the debtor and the creditor against failed SCT and to ensure that parties are aware of the Legal requirement for successful SCT in Nigeria. This paper recommends that the age of infants should be reviewed and made uniform across the country and that there should be a possibility to have a thorough investigation of the title of landed properties online. Keywords: Creditor, Debtor, Loan, Property, Secured Credit Transaction 1.Introduction In the modern world, Secured Credit Transaction (SCT) seems inevitable, especially for persons who are into business. There is a need to raise capital from time to time to enhance business and finance certain projects. People approach different sources of credit, ranging from individuals to financial institutions such as microfinance banks. The source being approached for credit seeks security to ensure that the loan, which will now include principal and interest, will be paid as when due. To have a legally recognized SCT, the parties must comply with specific legal requirements. This paper explores who the parties to the SCT are, what the law says about the capacity of each party, and the measures to be taken legally by the parties to ensure the three pillars of security: protection, assurance, and indemnity put in place. This paper is divided into three sections. The first part gives an insight into who the parties to the SCT are; the second part looks at the necessary steps to be taken to ensure the validity of SCT agreements and lastly, the third section gives a succinct conclusion and necessary recommendations that would provide the smooth running of SCTs in Nigeria. This paper will undertake a doctrinal research design to analyze the topic properly. 2.Parties to Secured Credit Transactions For the sake of this paper, the following are considered necessary parties to the SCT: Secured creditor; Debtor; Guarantor; Loan debt; Security; Secured creditor A creditor, according to the Cambridge dictionary, is ‘someone who the money is owed to’.[1] This is the person from whom the debtor has borrowed money and has given security to make room for the assurance that his money will be repaid, that security is protected, and that even if his money is not paid, he will get his money from the sale of the security and as such he will be adequately indemnified. In a mortgage transaction, he is the mortgagee in the simple term, he is referred to as the lender. Where the creditor is a bank, there is a restriction placed on the bank with regard to how much it can give out as a loan.[2] Hence people in charge of loans in the bank should ensure that they do not, out of excitement, give more than the amount that is legally allowed, as loan. Debtor The Cambridge dictionary defines a debtor as ‘someone who owes money’.[3] This is the party who owns the collateral and has secured it as evidence for the payment of a loan he took. He has an interest in the property and has agreed to do away with the interest he has if he is unable to repay the loan. Therefore, depending on the type of secured credit transaction, he can be referred to as the mortgagor as in the case of a mortgage transaction or, in simple term as the borrower. Guarantor The Cambridge dictionary defines a guarantor as a person who makes certain that something happens or that something is protected’.[4] A guarantor may be the owner of the security or someone standing as surety for the debtor. If the debtor is not a customer of a particular financial institution, he would need a surety. A surety must be a customer of the financial institution facilitating the loan and meet a certain required financial status.[5] Also, when the debtor does not have a property commensurate with the loan about to be taken from the creditor, a guarantor is needed; in this case, the guarantor uses his property instead and agrees to be liable should the debtor be unable to repay the debt.[6] The Loan debt Debt has been defined as “Something, especially money that is owed to someone else…”[7] The debtor is expected to pay the loan debt to the secured creditor. It is the money the secured creditor has advanced, and the debtor has given security. The loan debt is usually comprised of the principal sum, the original sum advanced by the secured creditor, and the interest, which is a particular percentage of the principal sum paid as profit on the loan to the secured creditor. The best practice is for the debtor to pay the interest in lump sum as soon as the SCT starts, and he then pays the principal sum in installments; this practice is known as amortization.[8] The Security Security is an asset that is promised by the debtor as protection in case he defaults on the reimbursement.[9] Section 1 (3) (b) (ii) of the Failed Banks Act (FBA)[10] prohibits naked lending by banks. A secured creditor has priority over an unsecured creditor,[11] and this was upheld in First Bank Nigeria Plc v. Nigerian Deposit Insurance Corporation.[12] Therefore a borrower needs to give security before he can be granted a loan. 2.1 Legal Capacity of Certain Parties SCT places no restrictions on anybody legally allowed to enter into contracts in Nigeria from being a party to an SCT. It follows that once a person can enter into a contract, he can enter into SCT because it is a form of contract. This further implies that the provisions guiding the capacity of specific categories of parties to a contract also govern those categories when they are involved in SCTs. Infants In Nigeria, a person under twenty-one (21) cannot enter a legal contract.[13] Any contract with an infant will be declared null and void and unenforceable against the infant. A mortgage involving an infant is void and cannot be enforced against the infant.[14] For an infant to be involved in any contract, he must involve a guardian. While this provision seems to protect the infant, it remains questionable if it is realistic and in line with modern practice. In recent times it has been experienced that people under 21 are exposed and mature and can make good decisions for themselves. Some of them are already university graduates and are working. If they can be allowed to work, make money, and save, it becomes a question what then is preventing them from owning properties and being parties to any form of an SCT? Persons above 18 can vote in Nigeria[15] and be held liable for any offense they commit. If they can take responsibility for their actions, if they can make decisions as to who the leaders in a country should be, then they should be able to make personal life decisions such as when to take a loan and how they choose to go about it and be allowed to take responsibility for any default. The traditional provision (especially under customary and Islamic law), which was upheld in Labinjo v. Abake[16] that the contractual capacity of a person under customary law begins at puberty and can be determined by the physical development and maturity of the person involved seems a better provision than the strict provision generalizing that all persons under 21 cannot make decisions involving SCT. It is suggested that the contractual age be reviewed and each person dealt with on an individual basis considering the person’s intellectual capacity, level of education, and area of growth, among others. Illiterates There is no general definition of who an illiterate is in Nigeria. However, it can be said and as held in some cases[17] that a person who does not understand the language of the agreement is illiterate. Like every other person, illiterates can exercise contractual capacity subject to certain formalities being complied with while preparing the contract agreement. An illiterate jurat must be inserted in any agreement involving an illiterate. The jurat must state that the terms of the agreement have been read to the illiterate in a language he understands and explained to him, and he signed the agreement upon a full understanding of the terms. So, an SCT agreement involving an illiterate must have an illiterate jurat. This provision seems fair to avoid the manipulation of people who do not understand the language of the contract. People with Unsound Mind The general rule is that people with the unsound mind can enter into a contract during their lucid interval.[18] However, a secured credit transaction entered into with a person of unsound mind is valid and only voidable at the instance of the borrower if the secured lender was not aware of the insanity or void if the unsoundness of mind is such that the transaction should not have happened at all.[19] The term unsound mind has been opined to be a broad term that covers numerous cases. It becomes questionable if a general law should govern all forms of unsoundness of mind cases in relation to the contract. Corporations A company is a legal person and, as such, has contractual capacity. However, the capacity of a company is limited by its memorandum of association and if a statutory company by the establishing statute. Any act outside the scope of the memorandum of association or the establishing statute is done ultra vires.[20] There is protection, however, for third parties who are involved in any act, conveyance, or transfer of property with a company if the sole reason for nullity of the transaction would be that it is ultra vires. Trustees Equity will not allow a trustee to unduly subject the trust property to financial risk, which would be to the detriment of the beneficiaries. Therefore, a trustee cannot borrow money using the trust property as security unless he is allowed to do so under the trust instrument.[21] He must, however, protect the beneficiary's interest at all times, even if he is permitted under the trust instrument to use the property as security. Relevant Matters to be taken into Consideration by the Secured Creditor to Ensure Validity of a Secured Credit Agreement A secured creditor must ensure that he takes certain steps and does certain things to ensure that the security truly belongs to the debtor and that he will be indemnified if repayment becomes impossible. Failure to do so may lead to a great loss to the creditor. They include: Having a Written Agreement For ease of reference and enforcement, an agreement evidencing a secured credit transaction should be in writing. There is a legal requirement for the mortgage agreement to be in writing. According to Section 4 of the Statute of Frauds 1677,[22] any transaction involving land must be in writing; failure to do so makes action arising from the transaction unenforceable.[23] The written document must contain the following to ensure its validity: the names and description of the parties, the description of the property, statement of the principal sum given as a loan, interest payable, time and mode of repayment, provision for redemption and other terms. The written document must be a deed; that it must be signed, sealed, and delivered by both parties. It must be elegantly drafted, and the execution must be properly done by all parties such that parties who require extra measures to be contained in their execution clauses should not have the special contents missing, such as illiterate jurat. Investigation of Title In the case of mortgage transactions, there are steps that the mortgagee can follow to ensure the safety of the security. They are:[24] Physical inspection: the mortgagee should visit the land that has been used as security and ensure that the land exists, is located where stated, and does not have any encumbrance that would prevent a sale should a sale arise. E.g., a tomb; Traditional evidence: if the land is a family land or communal land, the mortgagee should search with the principal members of the family or community leaders, ensuring that they have given their consent to the transaction to avoid difficulties during enforcement; Search at the land registry: Land Instrument Registration law establishes a land registry in each state. It is a place where documents relating to land are kept because, under the Land Use Act,[25] ownership of all lands in a state is vested in the governor of that state; any transfer made in respect of any land must be registered. A mortgagee should search at the land registry (usually for a fee) as this will show if there is any encumbrance, such as if the land has been mortgaged to another creditor; In Lagos and Abuja, it is important to get the consent of the owner of the land before a search can be conducted. This is a good practice and should be done in all states as this would put the mortgagor in check and may even urge him to be honest with the mortgagee; Search at the company registry: where at any point in time the land has been owned by a company registered under Companies and Allied Matters Act, or the mortgagor is a company, search should be conducted at the company registry, as this would help the mortgagee to know if the mortgage is ultra vires or not; Search at the Probate Registry: the mortgagee should ensure that the mortgagor if he got the land through a testamentary document has been granted probate in respect of the land. Mere having his name in the will does not connote transfer of ownership to him;[26] Court judgment: from time to time lands are subject to disputes in court and land disputes take years in most cases before they are settled. A search by the mortgagee at the court where he can obtain the certified true copy of any judgment relating to the land where necessary can save him from the mortgagor using a land already subjected to litigation and to which he can possibly loose ownership or may have lost ownership and probably appealing the case, as security. Valuation of Property Valuation is ‘the analytical process of determining the current worth of an asset or a company’.[27] It is done to determine the fair value of a property.[28] This is a procedure expected to be done by the secured creditor to ensure there is a margin of safety and that he never suffers a loss if the need for the sale of the property arises. The secured lender should ensure the valuation report makes provision for the following, among others:[29] state of the economy as at the date of valuation, location of the property, physical features, suitability of the property for lending, demand for the property, valuation method used, the amount the property is worth now and proposed worth after the term of the loan and so on.[30] Compliance with Planning Regulation Planning regulation is a system of land use restrictions and proposals regulating the exploitation and development of land in a particular place.[31] In Nigeria, the planning law is the Nigerian Urban and Regional Planning Act.[32] It has become pathetic that one main challenge of real estate in Nigeria is the lack of compliance with planning regulation provisions. Several builders and landowners are not even aware of the existence of planning regulations, and they go ahead to build houses where houses should not be built, places that should be commercial areas are made into residential and vice-versa; people build where roads should be constructed and so on. All these are violations of planning regulations and, in turn, lead to the destruction of property by the government, disaster such as fire outbreak which is often uncontrollable, and so on. It is expected that landowners should seek planning permission before constructing on land. The mortgagee must ensure that the land or building being used as security is effectively covered by planning permission and that the planning permission is religiously obeyed, not the case that a planning permit is obtained for a bungalow to be built and a story building is built instead. Immediate or Subsequent Acquisition The constitution provides that every citizen of Nigeria has the right to own both moveable and immovable property.[33] Also, as earlier stated, ownership of all lands is vested in the Governor of a state. This means that although a Nigerian can own land, such right is subject to the interests of the Governor of a state and hence the reason why any form of alienation without the Governor’s consent is prohibited.[34] The Governor reserves the right to take possession of the land at any point in time for overriding public interest.[35] Examples of overriding interests are:[36] exclusive government use or for general public use, use in connection with sanitary improvements of any kind, land required for mining purposes and so on. The statutory owner of the land has a right to be informed of the acquisition and, as such, must be given a personal notice of revocation of his right of occupancy stating the reason for the acquisition and that compensation would be paid.[37] The statutory owner can protest acquisition is not within the confines of the overriding public interest. A mortgagee should ensure that the land is not already subject to the acquisition or, if subject to acquisition during the terms of the loan, that he is aware and duly compensated. He can confirm this by checking the red copy of the survey plan and being sure that the term “free from acquisition” is boldly written on it. Integrity Test The lender must conduct an integrity test on the debtor to ensure that he is a person of his own words and he is truly who he parades himself to be. If he claims to own certain properties or has certain social and political connections, the secured creditor should investigate and be sure the information is accurate. Where the lender is a company such as a financial institution, the directors and managers of the bank must ensure that due diligence is put in place to ensure the borrower's integrity. They should ensure that loans are not granted to insolvent persons.[38] This is essential because, according to Section 12 (2) of the Failed Banks Act, directors, shareholders, and corporate officers of banks are liable for any loss the bank runs into because of unprofessional lending practices. There Must be a Provision for Insurance of the Security An insurance provision in the loan agreement is made to provide for what will happen in the event of any damages or destruction done to the property. It is an essential provision because the transaction is dependent on security. Any damage or destruction to the property would adversely affect the right of the parties, and in most cases, the mortgagee would be the one to experience the most significant loss because he may not be able to recover the mortgage debt and also the security with which he would have sought indemnification has been destroyed. Content of an insurance provision The party to insure the property in whose name the insurance policy will be taken out. It is advisable that the secured creditor insures the property during the term of the loan and then charge the debtor the premium paid with the loan debt. If, on the other hand, the debtor insures, the secured creditor should be made his lawful attorney so that he can also access the money upon damage to the property. With regards to Mortgage by deed, the mortgagee has the right to insure and keep insured against loss or damage by fire any building, or any effects or property of an insurable nature…and the premium paid for any such insurance shall be in a charge on the mortgaged property or estate or interest, in addition to the mortgage money.[39] The risk to be insured against and this is determined by the use to which the property is put, the location of the property, e.g., is it erosion-prone, is it in a flooded area etc. the nature of the property, and if there is the existence of any government policy, e.g., the government could state that all property in a certain area must be insured against fire. The insurance company to be used and must be a reputable company. The amount of the insurance premium must not be an outrageous amount of money. The date of commencement of the insurance policy. The duration of the policy must be clearly stated, and the secured creditor should ensure it covers the term of the loan. The application of the insurance money in the event of damage, whether to use it to reinstate the property or not. If the secured creditor has done the insurance, the secured creditor, upon receipt of the insurance money, would disburse the funds first to pay off the principal sum and interest owed him by the debtor and then render the remaining amount to the debtor. As such, the mortgagee would not have to wait to reinstate the damaged property as this may never happen or may take time and make it harder for the creditor to enforce the loan agreement. The parties may agree that the application of the insurance money in the event of damage should be made in such a way that it will negate S.67 of the Insurance Act,[40] which provides that every property that is destroyed by fire must be reinstated. Whatever the case may be, the parties are expected to agree on applying the insurance money to avoid dispute. The provision for insurance is essential because if there is no insurance provision, the creditor will lose the security to damage and not be entitled to any reimbursement because he cannot compel the debtor to surrender the insurance money to him if damage occurs to the property. 4. Conclusion SCTs are delicate transactions; they involve the parties to be extra careful and exercise due diligence to ensure that the transactions run smoothly. The basic legal requirements are put in place to ensure that the secured creditor and the debtor are both safe regarding the transaction. There are several provisions on due diligence to be expected from the parties involved legally while the law protects the mortgagor with the phrase “once a mortgage always a mortgage”[41] and some other rights to ensure he is not manipulated because of urgent need for money, the law also protects the mortgagee who is expected to ensure that the collateral is secured and once secured he can use it to enforce his right under the transaction agreement and he must be seen to be indemnified. The capacities of different parties were discussed, and specific questions and suggestions were made on the position of law concerning the ability of some parties to be involved in SCTs hence till any amendment is made the SCTs should not affect those stipulated not to be applied to avoid suffering a loss that could have been prevented. 4.1 Recommendations The age of infants should be reviewed and made uniform: there are various provisions on the age of persons who fall within the infant category in Nigeria. There is the age stipulated in the Electoral Act. There is an age specified in the Child Right Act and an age defined in the Infant Relief Act. It is believed that a general age should be adopted, and a law should be made to this effect; this law should also replace the outdated Infant Relief Act of 1874. Awareness for planning regulations: one of the significant problems with the enforcement of laws in Nigeria is the lack of understanding of the existence of those laws. Efforts should be made to educate the members of the public about the laws in existence, how they apply to them, the reasons for enacting them, and the consequences of not complying with them. Title investigation should be made easier through online platforms: in developed countries, information about a particular sector is found online. Information about every land in Nigeria should be made available in an online database which should be created for the land registry. Every transaction that has occurred or is occurring with land should be on the database. That way, investigation of the title would be done easily and more effectively. Bibliography Statutes Banks and Other Financial Institutions Act CAP B3 Laws of the Federation of Nigeria, 2004. Companies and Allied Matters Act Cap C20 Laws of the Federal Republic of Nigeria, 2004. Constitution of The Federal Republic of Nigeria 1999, CAP C3 Laws of the Federation of Nigeria 2004. Section 43. Conveyancing and Laws of Real Property Act 1881. Electoral Act 2010. Failed Banks (Recovery of Debts) and Financial Malpractices in Banks Act Cap F2 Laws of the Federation of Nigeria, 2004. Infant Relief Act 1874. Insurance Act 2003 Cap 4 Laws of The Federation of Nigeria 1990. Land Use Act Cap L5 Laws of the Federation of Nigeria 2004. Nigerian Urban and Regional Planning Act N0. 88 1992 CAP N138 Laws of the Federation Nigeria 2004. Property and Conveyancing Law Cap 100 Laws of Western Nigeria 1959. Statute of Frauds 1677. Books Dadem Y. Y, Property Law Practice in Nigeria (Jos University Press Limited 3rd Edition 2015). Smith I. O., Practical Approach to Law of Real Property in Nigeria (Ecowatch Publications Limited 2nd 2007). Dictionary Cambridge Dictionary, ‘Creditor’. <https://www.google.com/search?q=cambridge+definition+of+creditor&rlz=1C1CHBD_enNG883NG884&oq=cambridge+definition+of+creditor&aqs=chrome..69i57.58590j0j7&sourceid=chrome&ie=UTF-8 > [Accessed 06 January 2023]. Cambridge Dictionary, ‘Debtor’. <https://www.google.com/search?rlz=1C1CHBD_enNG883NG884&sxsrf=ACYBGNTytXNtHH5V0umVh0FZ0iak-I78Rg%3A1581020993930&ei=QXc8XuW0OOiAhbIPiqC-4AU&q=cambridge+definition+of+debtor&oq=cambridge+definition+of+debtor&gs_l=psy-ab.3..0i71l8.350617.352125..353040...0.3..0.0.0.......6....1..gws-wiz.RWzwfNijJ44&ved=0ahUKEwil2eaV4r3nAhVoQEEAHQqQD1wQ4dUDCAs&uact=5> [Accessed 06 January 2023]. Journal Articles Adedamola O., and Akinjare O., and Opeyemi J, ‘What Lenders Want from Mortgage Valuation Reports: A Survey of Nigeria Banks’ (2013) 2 International Journal of Economy, Management and Social Sciences. Aluko B.T., ‘Reliability of mortgage valuation for institutional lending in Nigeria’ (2004) 8(4) Journal of Strategic Property Management 193-203. Okafor K, ‘Current Loans in Nigeria’ (2019) 3(3) International Journal of Family Business and Management. Omotola J. O., ‘Planning Law in Nigeria’ (1991) 13(4) Third World Planning Review. Online Materials Chen J, ‘Valuation Definition’. <https://www.investopedia.com/terms/v/valuation.asp> [Accessed 07 January, 2023]. Elton C. Mpi, ‘How to Investigate Land in Nigeria’. <https://legalpuzzles.wordpress.com/2017/08/03/how-to-investigate-title-to-land-in-nigeria/> [Accessed 05 January 2023]. Net Lawman, ‘What is meant by “security” on a secured loan’. <https://www.netlawman.co.uk/ia/security > [accessed 03 January 2023]. Nigeria Law Claz, ‘Capacity to Contract’. <https://nigerianlawclaz.blogspot.com/2017/07/capacity-to-contract.html> [Accessed 06 January 2023]. Footnotes [1] Cambridge Dictionary, ‘Creditor’. <https://www.google.com/search?q=cambridge+definition+of+creditor&rlz=1C1CHBD_enNG883NG884&oq=cambridge+definition+of+creditor&aqs=chrome..69i57.58590j0j7&sourceid=chrome&ie=UTF-8> [Accessed 06 January 2023]. [2] Banks and Other Financial Institutions Act CAP B3 Laws of the Federation of Nigeria, 2004 (BOFIA), Section 18. [3] Cambridge Dictionary, ‘Debtor’. <https://www.google.com/search?rlz=1C1CHBD_enNG883NG884&sxsrf=ACYBGNTytXNtHH5V0umVh0FZ0iak-I78Rg%3A1581020993930&ei=QXc8XuW0OOiAhbIPiqC-4AU&q=cambridge+definition+of+debtor&oq=cambridge+definition+of+debtor&gs_l=psy-ab.3..0i71l8.350617.352125..353040...0.3..0.0.0.......6....1..gws-wiz.RWzwfNijJ44&ved=0ahUKEwil2eaV4r3nAhVoQEEAHQqQD1wQ4dUDCAs&uact=5> [accessed 06 January 2023]. [4] Cambridge Dictionary, ‘Guarantor’<https://dictionary.cambridge.org/dictionary/english/guarantor> [Accessed 03 January 2023]. [5] Yusufu Yilzum Dadem, Property Law Practice in Nigeria (Jos University Press Limited 3rd Edition, 2015). [6] ibid. [7] Cambridge Dictionary, ‘Debt’ <https://dictionary.cambridge.org/dictionary/english/debt> [Accessed 03 January 2023]. [8] Alicia Tuovila ‘Amotization’ <https://www.investopedia.com/terms/a/amortization.asp> [Accessed 03 January 2023]. [9]Net Lawman, ‘What is meant by “security” on a secured loan’<https://www.netlawman.co.uk/ia/security> [Accessed 03 January 2023]. [10] Failed Banks (Recovery of Debts) and Financial Malpractices in Banks Act, Cap F2 Laws of the Federation of Nigeria 2004. [11] BOFIA Section 54. [12] First Bank Nigeria v. Nigerian Deposit Insurance Corporation (Federal High Court Lagos) Punch Newspaper, 28/7/17. [13] Infant Relief Act 1874, A Statute of General Application. Section 1. [14] ibid. [15] Electoral Act, 2010. Section 12. [16] 5 NLR 33. [17] Nigeria Law Claz, ‘Capacity to Contract’ <https://nigerianlawclaz.blogspot.com/2017/07/capacity-to-contract.html> [Accessed 06 January 2023]. Otitoju v. Governor of Ondo State (1994) 4 NWLR (Pt.340)518. [18] Hall v. Warren 32 E.R 738. [19] Johnson v. Simmonds (1961) 25 Con. (N.S) 319. [20] Companies and Allied Matters Act 2020 Section 44. [21] I.O. Smith, Practical Approach to Law of Real Property in Nigeria (Ecowatch Publications Limited 2nd edn. 2007). [22] A statute of general application. [23] United Bank of Africa v. Tejumola (1988) SCNJ 173. [24]Elton C. Mpi, ‘How to Investigate Land in Nigeria’ <https://legalpuzzles.wordpress.com/2017/08/03/how-to-investigate-title-to-land-in-nigeria/> [Accessed 05 January 2023]. [25] Land Use Act Cap L5 Laws of the Federation of Nigeria 2004. (LUA) Section 1. [26] Elton (n14). [27] James Chen, ‘Valuation Defintion’< https://www.investopedia.com/terms/v/valuation.asp> [Accessed 07 January, 2023]. [28] ibid. [29]Oluwunmi Adedamola and Omolade Akinjare and Joshua Opeyemi, ‘What Lenders Want from Mortgage Valuation Reports: A Survey of Nigeria Banks’ (2013) 2 International Journal of Economy, Management and Social Sciences. [30] ibid. [31]J.A. Omotola, ‘Planning Law in Nigeria’ (1991) 13(4) Third World Planning Review. [32] N0. 88 1992 CAP N138 Laws of the Federation Nigeria 2004. [33] Constitution of the Federal Republic of Nigeria 1999, CAP C3 Laws of the Federation of Nigeria 2004. Section 43. [34] LUA Section 22. [35] LUA Section 28. [36] LUA Section 51 [37] Olatunji v. Military Governor of Oyo State (1994) LPELR 14116. [38] CAMA Section 280. [39] Property and Conveyancing Law, Cap 100 Laws of Western Nigeria 1959 Section 123 (1) (ii), Conveyancing and Laws of Real Property Act 1881 Section 19 (1) (ii). [40] Insurance Act 2003 Cap 4 Laws of the Federation of Nigeria 1990. [41] Owoniboys Tech. Services Ltd v. Union Bank of Nigeria Ltd (2003) JELR 15757 (SC).